THE EFFORT DEFINITION FOR LONGITUDINAL SLIDING OF TWO-AISLE CONTINUOUS AISLE BUILDING - Zakora, O. L.; Kliuchnyk, S. V.; Marochka, V. V. (Science and Transport Progress, 2008)
Variations of stresses in cross-sections of a launching girder and a span at all stages of its longitudinal shifting are investigated in the paper.